PERBEDAAN KEMANDIRIAN BELAJAR ANTARA MAHASISWA BIDIKMISI DAN NON BIDIKMISI DI PROGRAM STUDI PENDIDIKAN EKONOMI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU 2018/2019 - Rahma Kartika Sari; Gimin Gimin; Mujiono Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the comparison of learning independence between Bidikmisi students and non-Bidikmisi students in the Department of Social Sciences, Faculty of Teacher Training and Education, University of Riau 2018/2019. The population in this study was divided into 2 groups, namely: Population in Bidikmisi students is 66 people, because the population of Bidikmisi students is less than 100 people, so it uses census sampling techniques in which all populations are sampled. The population of non-bidikmisi students is 257 people, because the population of non-Bidikmisi students is more than 100 researchers using the Slovin formula approach, so that by using the Slovin formula we can determine a sample of 72 people. The datas used are primary datas, namely through questionnaires. The study used quantitative methods and similarity test analysis of two averages / different tests. Based on descriptive analysis, student learning independence bidikmisi University of Riau Economic Education is in the high category, amounting to 26 students (39.39%) while Non Bidikmisi Student Learning Independence is in the low category, amounting to 31 students (43.05%). Based on the Independent Samples Test (Difference Test), obtained the significance value of the F test is 0.110 which means the variance or distribution of the two samples is the same or homogeneous, then the test used is Equal variances assumed. The results of the t test of significance value (2-tailed) are 0.04. Because the value is smaller than 0.05, it can be concluded that there is a difference between the learning independence of Bidikmisi students and non-Bidikmisi students.Key Words: Learning Independence and Bidikmisi